VIOLATING MAXIMS IN PRESIDENTIAL DEBATE BETWEEN PRESIDENT OBAMA AND REPUBLICAN NOMINEE MITT ROMNEY - Juniar Selpiana; Sumarsih Sumarsih (LINGUISTICA, 2012)
ABSTRACT The study deals with the types of maxims violation in Presidential Debate between President Obama and Republican Nominee Mitt Romney on October 3, 2012. The objectives of study are to describe the violated maxim, to derive the dominant violated maxim and to reason for the use of dominant violated maxims in presidential debate. The data is the transcript of the presidential debate and taken from the internet. This research is conducted by using descriptive qualitative design. It is found that there are 65 utterances violated by the candidates. The results of data analysis show the total numbers are: maxim violation of quantity (67.69%), quality (23.07%), relevance (6.16%), and manner (3.08%). The most dominant type of maxim violation is quantity because the candidates give the information as much as possible to clear up and ensure the listener(s) that one of them is the best choice to be the next American president.   Keyword        : Gricean Maxims, cooperative principle, violating maxims